Pre- and Post-surgical Poor Seizure Control as Hallmark of Malignant Progression in Patients With Glioma? - Pauletto, Giada; Nilo, Annacarmen; Lettieri, Christian; Verriello, Lorenzo; Tomasino, Barbara; Gigli, Gian Luigi; Skrap, Miran; Ius, Tamara (Frontiers in Neurology, 2022)
Background: Regarding brain tumor related epilepsy (BTRE), there are growing evidence about a relation between epileptogenesis and oncogenesis. A recent study suggests a role of post-surgery seizure outcome on the survival of low-grade glioma (LGG) patients, underlying the need for a targeted and aggressive epilepsy treatment. Objective: The present study aims at investigating the possible correlation between pre- and post- surgical seizure control and tumor progression in patients who underwent surgery for LGG. Methods: We performed a retrospective analysis of patients affected by LGGs and BTRE, in a single high-volume neurosurgical center. Seizure control was assessed before surgery and at 3 years follow-up. Patients with histological progression in high-grade glioma (HGG) have been evaluated. Clinical features, pre-surgical electroencephalograms (EEG) and electrocorticography (ECoG) have been analyzed. Results: Among 154 subjects, we collected 32 patients who presented a tumor progression in HGG during the follow-up period. The majority had poor seizure control both pre- and post-surgery, never being in Engel class Ia throughout the whole history of their disease. Almost all patients with poor seizure control had pathological ECoG recording. Clinical features of seizures did not correlate with seizure outcome. On the univariate analysis age, post-operative Engel class and EOR were prognostic factors significantly associated to oncological outcome, nevertheless on multivariate analysis Engel class significance was not confirmed, and the only predictor factors were age and EOR. Conclusions: Although not confirmed on multivariate analysis, post-surgical seizure control could be a relevant factor to be considered during follow-up of BRTE, in particular when gross-total resection is not achieved. Pathological findings on the ECoG may suggest a “hidden” propensity to malignant progression, strictly related with persistent neuronal hyper-excitability. Further studies with longer follow-up period are needed to confirm our observations.